4 - TENTATIVES DE STABILISATION ECONOMIQUE AU ZAIRE - KASONGO MUNGANGA, (Africa Development, 1979)
Since price increase has always been considered as a sign of malistration, anti-inflationist policy has become the priority of priorities in almost all market economy countries. Such is the case in Zaïre where three economic stabilization attempts have been tried. In the first part of his article, the writer deals with the general aspects of political stabilization: the very nature of stabilization, the causes of inflation and the different political anti-inflationist means. In the second part, he identifies the social classes which profit from inflation in Zaïre (importers, other traders-people, currency traf fickers and loan-makers) as well as the social categories which suffer from it (export firms, local consumers and wage-canners, foreign and local investors, the State itself). ln the third part, the writer tries to find the deep causes of the inflations which have led to the stabilization attempts of 1963-64, 1967-68 and 1976. He analyses the policies which have been used and the results obtained. He draws the conclusion that all the means which have been used to combat inflation wi11 be inefficient or even in case they succeed, the success will be very brief because the problems of the Zairian economy are first of all structural. In the fourth part, he gives more precision about: - The economic structures which have an impact on stabilization and which must be transformed if the combat against inflation is to be successful; - The changes which the structures of the home production have to undergo since it is still essentially based on primary products the fluc tuation prices of which are higher than those of industrial products. - The changes in the economic relations with foreign countries, rela tions directed mainly to Belgium up to now. This situation makes it easy for rapid repercussion of salary increases and other inflation factors on the Zairian economy (imported inflation) . - The transformations in the national economic space: 8 percent of the productive national ressources are shared between the Shaba and Kinshasa regions so that as soon as one of these two regions is affected economically, the economic instability is felt throughout Zaire.